GREEN PURCHASE DETERMINANTS BASED ON INTERPRETIVE STRUCTURAL MODELING: CASE OF IRAN’S GREEN MARKETING - Nayeri, Mahmoud Dehghan; Moradi, Mohammad (ASEAN Marketing Journal, 2021)
Manuscript type: Research paperResearch Aims: This paper aims to clarify the relationship between the green purchase behavior’s affecting factors as well as organizing them depending upon their driving and dependence power which ultimately leads to an ISM-based structural model.Design/methodology/approach: Thorough literature review and subsequent discussions with experts, antecedent factors of green purchase behavior are extracted, which are followed by ISM structural modeling.Research Findings: Interpretive structural modeling, justified a five-layer structure in which the role of government, social influence, and reference power are the cornerstones of green purchase behavior in Iran’s green market.Theoretical Contribution/Originality: As the general rule of all affecting factors in stimulating green purchase behavior of customers, this is a rare study which investigates and provides insights to clarify the exact role of the factors in the field, including driving, linkage, autonomous and dependent variables.Practitioner/Policy Implication: Scrutinizing the motivators of green purchasing behavior and their interrelationships would help professionals as well as scholars to understand its determinants, which will lead to more insightful decisions. Further, this understanding may be useful in shaping green marketing policies and strategies for Iranian and the other green product firms al around the world.Research limitation/Implications: the limitation of this study was twofold: first, as purchasing green products is not isolated from cultural context, this study has been conducted in a green purchase cultural context which is in developing phase; Second, reaching to academia experts was another limitation of the study as there has been a lack of in-depth study in this field by Iranian academics.